Role of Gum Chewing After Small Gut Anastomosis - Usman Qureshi , Muhammad Salman Shafique , Jahangir Sarwar Khan , Dr Sarosh Afzal Farooqi, Usman Qureshi , Muhammad Salman Shafique , Jahangir Sarwar Khan , Dr Sarosh Afzal Farooqi (Journal of Rawalpindi Medical College, 2019)
This study was performed to access the effectiveness of gum chewing on gut motility in early postoperative period after small gut anastomosis in patients operated for reversal of ileostomy or ileocolostomy. Methods: This prospective, randomized trial was undertaken at Surgical Unit-I, Holy Family Hospital, Rawalpindi Medical University, Rawalpindi from March 2016 to March 2018. 90 patients were randomly divided into two equal groups. All patients underwent small gut anastomosis after reversal of ileostomy or ileocolostomy. In group A (gum chewing group), patients were advised to chew gum, whereas group B (control group) patients did not received any gum for chewing and continued standard post-operative care. Both groups were kept NPO till 2nd post-operative day. After surgery, all patients were observed for onset of bowel sounds, time after surgery when flatus and stool were passed, time required for return of appetite and discharge from hospital. Patient satisfaction with postoperative course, incidence of anastomotic leak, wound infection and mortality was also recorded in both groups. Results : Statistically, group A and group B were similar in age, gender and type of procedure. There was significant difference between both groups for onset of bowel sounds, passage of first flatus, complaints of nausea and vomiting, appetite, duration of hospital stay and patient’s satisfaction level (P < 0.05). In Group A, 35 patients were satisfied whereas in group B, only 5 patients were happy with their postoperative course (P < 0.05). There was no statistically significant difference between groups for incidence of anastomotic leak, wound infection and mortality. Conclusion: It is safe and cost effective to advise gum chewing in patients undergoing small gut anastomosis for reducing duration of postoperative ileus and improving level of patient satisfaction about their postoperative course. Keywords: Postoperative ileus, Ileostomy, Anastomotic leak, Surgical site infection